The Relationship Between Work-Life Balance and Job Satisfaction Among Generation Z in the Start-Up Sector - Leni Gustina; Mahamudul Hasan; Kabiru Jinjiri Ringim (Takaza Innovatix Labs Ltd., 2025)
This study examines the relationships between work-life balance, organizational support, job satisfaction, and retention intention, with employee engagement as a mediating variable, focusing on professional players in the ARTEX E-SPORT team in Padang. Utilizing a quantitative research design with a saturated sampling technique involving 35 respondents, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results reveal that work-life balance has a strong positive effect on job satisfaction and retention intention, while organizational support significantly influences both outcomes and enhances employee engagement. Furthermore, employee engagement mediates the relationships between work-life balance, organizational support, and the dependent variables, highlighting its critical role in linking supportive workplace practices to employee outcomes. These findings emphasize the importance of fostering a balanced and supportive work environment to enhance engagement, satisfaction, and retention, particularly for Generation Z employees in high-demand sectors like esports. This study contributes to existing literature by exploring these dynamics in the esports industry and provides actionable insights for organizations to implement effective workforce management strategies. Future research is encouraged to include additional mediating or moderating variables and explore these relationships across diverse organizational contexts.